Trust In A Hybrid Recommender Systems - Karimi, Morteza (2011)
In this research,a novel trust calculation that is incorporated into a hybrid recommender system is proposed in order to increase the accuracy of rating prediction. The accuracy of the proposed system was measured based on Recall and Precision.